ALUR DALAM DEMAIN KARYA GUILLAUME MUSSO - Petrus, Jeni; Yolanda Latjuba, Ade; Hasbullah, Hasbullah (Universitas Hasanuddin, 2019)
This study aims to analyze the flow of story sequences in the Demain novel by Guillaume Musso. The analysis shows that the interplay of the past and the present events is one narrative strategy to incite the the curiosity of the readers on the one hand and to delay the possible logic of the sequential story. The results of this study show that the structure of the text contained in the novel Demain can be divided into two main parts, namely: The first part is the group of pre-marriage events that occurred in the years of respectively 1991,1992,1993,1994,1996,1998,1999. While The second stage is the period of the marriage between Matthew and Kate in the year. 2006, The accidental event of old computer purchase by Matthew, the main character leads to a new dimension that opens the way to retrospect the old events.